2004
DOI: 10.3171/foc.2004.17.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery in patients with glomus jugulare tumors

Abstract: Object Microsurgical removal of glomus jugulare tumors is frequently associated with injury of the lower cranial nerves. To decrease the morbidity associated with tumor management in these patients, gamma knife surgery (GKS) was performed as an alternative to resection. Methods Between 1990 and 2003, 42 patients underwent GKS as the primary management (19 patients) or for recurrent glomus jugulare tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 17 publications
4
57
0
4
Order By: Relevance
“…For these studies, 95% of patients (95% CI, 90-98%) achieved clinical control and 96% (95% CI, 92-98%) achieved tumor control. In contrast, 11 studies reported a mean or median follow-up time of <36 months (12,13,16,17,24,25,27,28,29,33,34,38,39,42,43). For this group, 98% of patients achieved tumor control (95% CI, 95-100%) and 95% (95% CI, 91-98%) achieved clinical control.…”
Section: Resultsmentioning
confidence: 97%
“…For these studies, 95% of patients (95% CI, 90-98%) achieved clinical control and 96% (95% CI, 92-98%) achieved tumor control. In contrast, 11 studies reported a mean or median follow-up time of <36 months (12,13,16,17,24,25,27,28,29,33,34,38,39,42,43). For this group, 98% of patients achieved tumor control (95% CI, 95-100%) and 95% (95% CI, 91-98%) achieved clinical control.…”
Section: Resultsmentioning
confidence: 97%
“…Neurological improvement occurs in 24-39% of the cases, and a few cases experience worsening of conditions (only 2.8% permanent; Gottfried et al 2004, Suarez et al 2013a). However, new hearing loss is reported in up to 19% of the SRS-treated JPGL cases (probably due to bone radiation injury; Pollock 2004). JTPGL tumour control with SRS or EBRT is not statistically different, but the mortality due to disease or treatment has been reported to be significantly lower for SRS (Suarez et al 2013a).…”
Section: Radiotherapymentioning
confidence: 99%
“…However, the median follow-up duration is short (2-4.8 years), so long-term true local control cannot be accurately assessed. Symptomatic improvement is frequent (29-70%), and a new CN deficit or worsening of a pre-existing CN deficit occurs rarely (0-15%) (Liscak et al 1999, Foote et al 2002, Pollock 2004, Lieberson et al 2012. In a recent literature review, the overall control rate has been reported to be 98% (mean follow-up duration of only 31 months) with a 3% overall complication rate (mostly mild: nausea, vomiting and vertigo) (Lieberson et al 2012).…”
Section: Radiotherapymentioning
confidence: 99%
“…Emollitio cerebri és agyidegbénulások lehetnek az intervenciós beavatkozás főbb szövődményei [6,8]. Inoperábilis esetekben potenciális kezelési lehetőség a stereotaxiás sugársebészeti kezelés, amellyel általában jó növekedési kontroll érhető el [9,10].…”
Section: Glomus Jugulare Tumorunclassified